Population structure of the broad-snouted caiman (Caiman latirostris) in natural and man-made water bodies associated with a silvicultural landscape - Marques, Thiago Simon (2016)
The broad-snouted caiman (Caiman latirostris) is a South American crocodilian with a wide geographical distribution. Water bodies originally occupied by the species have suffered extreme anthropogenic pressure; however, the broad-snouted caiman has a high adaptive capacity to colonize man-made habitats such as decanting pounds and artificial reservoirs for agriculture or livestock. In this context, the present study aimed at identifying the population structure of the broad-snouted caiman in a silvicultural landscape in southeastern Brazil. Fifty-two caimans of various classes were captured with baited traps and steel cable snares at night. The estimated population size was 51 individuals. The population density was estimated to be 2.6 individuals/ha with a linear density of 11.3 individuals/km. The intermediate values of linear density estimates herein compared with other areas, suggesting that silvicultural landscapes can be relevant for broadsnouted caiman conservation. Therefore, the role of silvicultural landscapes in crocodilian conservation should be taken into consideration for environmental certification processes related to forestry in the Neotropics.